Kepemimpinan Kepala Madrasah dalam Pengembangan Infrastruktur dan Suprastruktur Pendidikan - Erlina, Sapta; Hakim, Lukman (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the leadership strategies of madrasah principals in developing infrastructure and suprastructure, despite their significant impact on improving educational quality, particularly at Madrasah Aliyah Perguruan Mu’allimat. The objective is to analyze the leadership strategies employed by the madrasah principal in developing physical facilities and strengthening organizational management systems. Employing a qualitative case study design, the research involved one purposively selected madrasah. Data were collected through interviews, observations, and documentation, then analyzed using descriptive analysis techniques. The findings reveal that the madrasah principal effectively applies participative and visionary leadership strategies in managing the development of infrastructure and suprastructure. These strategies reflect transformational leadership characteristics, emphasizing the leader’s role as a role model and motivator. In conclusion, the madrasah principal plays a central role in fostering communication and collaboration with various stakeholders to enhance educational quality. The study’s implications include theoretical contributions to the literature on Islamic educational leadership and practical recommendations for madrasah administrators to strengthen leadership capacity and resource management. Additionally, the research opens opportunities for further studies on the relationship between leadership and the sustainability of madrasah development.